Surface‐Acoustic‐Wave (SAW) Induced Mixing Enhances the Detection of Viruses: Application to Measles Sensing in Whole Human Saliva with a SAW Lab‐On‐a‐Chip. (7th July 2022) - Agostini, Matteo; Lunardelli, Francesco; Gagliardi, Mariacristina; Miranda, Alessio; Lamanna, Leonardo; Luminare, Antonella Giuliana; Gambineri, Francesca; Lai, Michele; Pistello, Mauro; Cecchini, Marco
Abstract: Measles is one of the most infectious airborne viruses worldwide. With a basic reproduction rate between 12–18, this virus is six times more infectious than the SARS‐CoV‐2 Alpha variant and similar to the SARS‐CoV‐2 Omicron variant. Even though a cheap and effective vaccine is available, measles is still common in developing countries. To date, sporadic outbreaks are also reported in developed countries, primarily due to non‐vaccinated people. This work presents a point‐of‐care (POC) biosensing device capable of detecting measles virions (MV) in human saliva. The device is a surface‐acoustic‐wave (SAW) based lab‐on‐a‐chip (LOC), smaller than a €1‐cent coin, in which SAWs are used both for sensing and fluid recirculation. The biosensing detection performance of this system is tested and device sensitivity and selectivity are assessed. The SAW‐LOC with MV loaded in healthy, whole human saliva is finally validated. The experimental results also highlight a crucial aspect of the biosensing process: the interactions between probing and target species during incubation with or without fluid mixing. The presented findings are promising for realizing a POC platform for measles diagnosis and may serve as a guideline for designing new microfluidics‐based biosensing systems. Abstract : Here, a surface‐acoustic‐wave (SAW) based lab‐on‐a‐chip (LOC) for detecting measles virions is presented, in which SAWs are used both for sensing and fluid recirculation. The biosensing detection performance of this system is shown and device sensitivity and selectivity is assessed. The SAW‐LOC with measles virions detection in whole human saliva is finally validated.